A study of breast cancer detection practices and beliefs in black women attending public health clinics - Duke, Suzanne S; Gordonsosby, Karen; Reynolds, Kim D; Gram, Inger T (Health Education Research, 1994)
In this study, breast cancer knowledge, beliefs and practices in low income black women were examined. First, focus groups were held with a total of 33 participants. Information gathered from the focus groups was used to develop a telephone survey which was partially based on the Health Belief Model (HBM) and administered to 92 subjects. Utilization rates of mammography and breast self-examination (BSE) were quite high; 66.3% of survey participants reported having at least one mammogram and 72.5% performed BSE. Because low-cost mammograms were available to the survey participants, these results suggest that women in this target population will utilize accessible and affordable mammograms. Several knowledge deficiencies that need to be addressed were also identified. Most of the health beliefs were not significantly associated with mammography or BSE utilization. Because the HBM has never been extensively tested on this population, its appropriateness as a behavior model for low-income women is examined. Implications for future research and interventions are discussed.
Keywords: *African Americans/px [Psychology]; *Breast Neoplasms/pc [Prevention & Control]; *Health Knowledge, Attitudes, Practice; Adult; Aged; Alabama; Blacks; Breast Neoplasms; Breast Neoplasms/eh [Ethnology]; Breast Neoplasms/px [Psychology]; Breast Self-Examination; Breast Self-Examination/px [Psychology]; Cohort Studies; Female; Human; Humans; Knowledge, Attitudes, Practice; Mammography; Mammography/px [Psychology]; Middle Age; Middle Aged; Support, U.S. Gov't, P.H.S.; adult; article; breast cancer; breast examination; cancer diagnosis; dept.hms; female; health survey; human; lowest income group; major clinical study; mammography; negro; outpatient department; priority journal; public health